Association between behavioural and psychological symptoms of dementia and residence status in patients with Alzheimer's disease. Issue 1 (26th October 2022) - Midorikawa, Haruhiko; Ekoyama, Saori; Tachikawa, Hirokazu; Ota, Miho; Tamura, Masashi; Takahashi, Takumi; Sekine, Aya; Ide, Masayuki; Matsuzaki, Asaki; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki
Abstract: Background: Examining the relationship between the behavioural and psychological symptoms of dementia (BPSD) and residence status is crucial to improving BPSD and reducing the burden on caregivers. However, studies on how BPSD differ between individuals living at home and those in institutional settings are lacking. We conducted a questionnaire survey among healthcare providers (HCPs) involved in dementia care and nursing to clarify the characteristics of BPSD by residence status in patients with Alzheimer's disease (AD) living at home or in facilities. Methods: We sent questionnaires to HCPs and asked them to answer questions on up to five cases that needed treatment for BPSD and who received long‐term care insurance services from 1 April 2016 to 31 March 2017. Responses were received for 371 cases, of which 130 diagnosed with AD were analyzed. The patients were divided into two groups: patients with AD living at home (home care group) and patients with AD living in facilities (facility care group). A Chi‐square test was used to identify differences between the two groups. A binomial logistic regression analysis was also conducted to clarify the association between residence status and BPSD. Results: Of the 130 patients, 72 lived at home (home care group) and 58 resided in facilities (facility care group). None of the background factors was significantly different between the two groups. The Chi‐square test indicated that sleep disturbance was significantly more common in the facility care group (60.3% in the facility care group vs. 33.3% in the home care group, P = 0.003), while the logistic regression analysis indicated that sleep disturbance was significantly associated with residence status (odds ratio: 2.529, P = 0.038). Conclusions: Sleep disturbances were more frequently observed among patients with AD living in institutions than among those living in their homes.